Clonal chromosome aberrations in myeloid leukemia after styrene exposure - Kolstad, Henrik A; Pedersen, B; Olsen, Jørn; Lynge, Elsebeth; Jensen, G; Lisse, I; Philip, P; Tinggaard Pedersen, N (Scandinavian Journal of Work, Environment & Health, 1996)
' ' OBJECTIVES ': 'The purpose of the study was to determine the risk of myeloid leukemia subclassified according to clonal chromosome aberrations in styrene-exposed workers.' ' METHODS ': 'A nested case-referent study was carried out on 19 myeloid leukemia patients, of which 12 showed clonal chromosome aberrations, and 57 referents ascertained within the Danish reinforced plastics industry and similar industries with no styrene exposure.' ' RESULTS ': 'A 2.5-fold increased risk for myeloid leukemia with clonal chromosome aberrations (95% confidence interval 0.2--25.0) was found among workers of companies with styrene exposure.' ' CONCLUSIONS ': 'The results suggest that styrene may cause leukemia through a clastogenic effect. But similar findings could also have been found if the exposure was associated with a specific subtype of leukemia prone to develop the chromosome aberrations in question. Due to the few observations and the lack of detailed exposure data, additional studies are needed to corroborate or refute the present suggestive findings.
Keywords: case-referent study; epidemiology; neoplasm; occupational exposure; organic solvent